The degree to which employees of the Ministry of Education in Jordan possess life skills from their own point of view - Alkasasbeh, Isam Radwan Salameh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of possession of life skills among the employees of the Ministry of Education in Jordan, and the descriptive analytical survey method was used. The Jordanian Ministry of Education, and the study concluded that the degree to which the employees of the Ministry of Education in Jordan possess life skills from their point of view obtained a total average (3.69 out of 5), i.e. a (high) degree. ) Then time management skills with an average, then time management skills with an average of (3.72), which are graded (high), and thirdly, self-esteem skills with an average of (3.67) and fourthly- communication and communication skills with an average of (3.64), and finally: decision-making and problem-solving skills with an average of (3.63) and these three The latter assessed possession with a degree (medium), as it was found that there were no statistically significant differences at the level (α≥0.05) between the sample’s views regarding the degree of possession of life skills by employees of the Ministry of Education in Jordan due to the variables (gender, educational qualification). While it was found that there were differences due to the variable of job experience, in favor of those with experience (10 years or more) versus those with experience (less than 5 years). Based on the results, the researcher presented a number of recommendations and proposals to raise the level of life skills possession of life skills by the employees of the General Diwan of the Ministry of Education in Jordan and the general staff of the ministry.
Keywords: degree of possession; life skills; Ministry of Education employees; Kingdom of Jordan